Risk factors associated with competing mortality among patients with head and neck cancer in Japan. (3rd March 2016) - Takenaka, Yukinori; Yasui, Toshimichi; Enomoto, Keisuke; Miyabe, Haruka; Morizane, Natsue; Ashida, Naoki; Shimizu, Kotaro; Hirose, Masayuki; Yamamoto, Yoshifumi; Uno, Atsuhiko
Abstract: Conclusions This study demonstrated a high incidence of competing mortality in patients with head and neck cancer (HNC). It identified age to be an independent prognostic factor for non-cancer mortality. These findings contribute to the appropriate treatment selection in clinical settings and study design in clinical trials. Objectives To investigate the incidences of second primary cancer (SPC) and non-cancer mortalities among patients with HNC and reveal the determinant factors for these mortalities. Methods This study reviewed the records of 334 patients with HNC between 2006–2012. The cumulative incidences of HNC, non-cancer, and SPC mortalities were estimated. A Fine and Gray regression model was used to investigate factors associated with cancer and non-cancer mortalities. Results The 5-year cumulative incidences of HNC, SPC, and non-cancer mortalities were 28.0%, 2.5%, and 6.5%, respectively. In univariate analysis, the factors associated with SPC mortality were tumor site and comorbidity, whereas those associated with non-cancer mortality were age, gender, and comorbidity. In multivariate analysis, age (sub-distribution hazard ratio = 2.59) was the independent risk factor for non-cancer mortality.